Features and difficulties of the ISA audit - M. N. Smagina; S. V. Malkova; A. S. Kuznetsova (Путеводитель предпринимателя, 2022)
The article examines the main features and difficulties of auditing according to international auditing standards. The topic is relevant, since such standards are already used in our country. At the same time, the process of their introduction was long and time-consuming. However, this did not lead to their implementation without significant difficulties. New legislative amendments in this area only prove that the topic is relevant. As a result of the work, a conclusion will be drawn about the problems of applying international auditing standards, without solving which their full use in our country is impossible.